P-element repression in Drosophila melanogaster by variegating clusters of P-lacZ-white transgenes. - Ronsseray, S.; Boivin, A.; Anxolabehere, D. (Genetics, 2001)
In Drosophila, clusters of P transgenes (P-lac-w) display a variegating phenotype for the w marker. In addition, X-ray-induced rearrangements of chromosomes bearing such clusters may lead to enhancement of the variegated phenotype. Since P-lacZ transgenes in subtelomeric heterochromatin have some P-element repression abilities, we tested whether P-lac-w clusters also have the capacity to repress P-element activity in the germline. One cluster (T-1), located on a rearranged chromosome (T2;3) and derived from a line bearing a variegating tandem array of seven P-lac-w elements, partially represses the dysgenic sterility (GD sterility) induced by P elements. This cluster also strongly represses in trans the expression of P-lacZ elements in the germline. This latter suppression shows a maternal effect. Finally, the combination of variegating P-lac-w clusters and a single P-lacZ reporter inserted in subtelomeric heterochromatic sequences at the X chromosome telomere (cytological site 1A) leads to strong repression of dysgenic sterility. These results show that repression of P-induced dysgenic sterility can be elicited in the absence of P elements encoding a polypeptide repressor and that a transgene cluster can repress the expression of a single homologous transgene at a nonallelic position. Implications for models of transposable element silencing are discussed.